Autoantibody testing in idiopathic inflammatory myopathies. Issue 4 (2nd March 2019) - Rietveld, Anke; Lim, Johan; de Visser, Marianne; van Engelen, Baziel; Pruijn, Ger; Benveniste, Olivier; van der Kooi, Anneke; Saris, Christiaan
Abstract : The diagnosis and classification of idiopathic inflammatory myopathies are based mainly on clinical and histological features. The discovery of myositis-specific and myositis-associated antibodies has simplified the (sub)classification of inflammatory myopathies. Patients suspected of having an idiopathic inflammatory myopathy should undergo routine antibody testing to gain more insight into distinct phenotypes, comorbidities, treatment response and prognosis. Furthermore, autoantibody testing can help in patients with atypical patterns of weakness or with an unresolved limb-girdle myopathic phenotype, or interstitial lung disease. However, some important technical and methodological issues can hamper the interpretation of antibody testing; for example, some antibodies are not included in the widely available line blots. We aim to provide a practical review of the use of autoantibody testing in idiopathic inflammatory myopathies in clinical practice.